Impact of salt intake and renin-angiotensin-aldosterone system blockade on lung severe acute respiratory syndrome coronavirus 2 host factors - Zhang, Xiaoli; Liu, Liping; Gaballa, Mohamed Mahmoud Salem Ahmed; Hasan, Ahmed A.; Xiong, Yingquan; Xie, Li; Klein, Thomas; Delic, Denis; Kleuser, Burkhard; Krämer, Bernhard; Li, Jian; Hocher, Berthold (Kidney & blood pressure research, 2022)
Introduction: The angiotensin-converting enzyme 2 (ACE2) as well as the transmembrane protease serine type 2 (TMPRSS2) have been found to play roles in cell entry for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the virus causing coronavirus disease 2019 (COVID-19). SARS-CoV-2 infection risk and severity of COVID-19 might be indicated by the expression of ACE2 and TMPRSS2 in the lung. Methods: A high-salt diet rat model and renin-angiotensin-aldosterone system (RAAS) blockade were used to test whether these factors affect ACE2 and TMPRSS2 expression in the lung. A normal (0.3% NaCl), a medium (2% NaCl), or a high (8% NaCl) salt diet was fed to rats for 12 weeks, along with enalapril or telmisartan, before examining the lung for histopathological alteration. Using immunofluorescence and qRT-PCR, the localization as well as mRNA expression of ACE2 and TMPRSS2 were investigated. Results: The findings provide evidence that both TMPRSS2 and ACE2 are highly expressed in bronchial epithelial cells as well as ACE2 was also expressed in alveolar type 2 cells. High-salt diet exposure in rats leads to elevated ACE2 expression on protein level. Treatment with RAAS blockers had no effect on lung tissue expression of ACE2 and TMPRSS2. Conclusions: These findings offer biological support regarding the safety of these drugs that are often prescribed to COVID-19 patients with cardiovascular comorbidity. High salt intake, on the other hand, might adversely affect COVID-19 outcome. Our preclinical data should stimulate clinical studies addressing this point of concern.
Gesehen am 12.09.2023